TAKHRĪJ AL-HADĪTH TERHADAP HADIS-HADIS DALAM BUKU FIKIH MADRASAH ALIYAH - Mukhamad Luqman Hakim; Ali Anwar (LPPM IAIN Kediri, 2022)
This research focuses on tracking the sources of hadiths contained in the book of Jurisprudent Madrasah Aliyah on the main hadith books as compiled by mukharrij and determining the quality of hadith. In order to trace the source and understanding of hadith is used the books of hadith written by mukharrijnya and sharh each of these books. While the references used to determine the quality of sanad, in which there is a narration, which leads to the quality of each hadith will be used the book rijāl al-hadīth. While the technique for determining the quality of hadith will be used the opinion of Jumhūr al-'ulamā', who argues that the terms and indicators of the validity of sanad hadith are the connected sanadnya, the quality rāwī 'ādil, rāwīnya dābit, avoid shudhūdh, and avoid 'illat. The results of this study found 933 sources of hadith from 151 hadith contained in the Book of Jurisprudency Class X, XI, and XII. Each hadith was found to an average of 6.18 hadith sources. Of the 151 sahīh li dhātihi quality hadiths as many as 101 (66.88%), Sahīh li Ghairihi as many as 2 (1.32%), Hasan li Dhātihi as many as 24 (15.89%), Hasan li Ghairihi as many as 2 (1.32%), and Da'īf as many as 22 (14.57%) Penelitian ini memfokuskan pada pelacakan sumber hadis-hadis yang terdapat pada buku Fikih Madrasah Aliyah pada kitab-kitab hadis pokok sebagaimana disusun oleh mukharrij dan penentuan kualitas hadis. Dalam rangka melacak sumber dan pemahaman hadis digunakan kitab-kitab hadis yang ditulis oleh mukharrijnya dan sharh masing-masing kitab tersebut. Sedangkan referensi yang digunakan untuk menentukan kualitas sanad, yang di dalamnya terdapat periwayat, yang berujung pada kualitas hadis masing-masing akan digunakan kitab rijāl al-hadīth. Sedangkan teknik untuk menentukan kualitas hadis akan digunakan pendapat Jumhūr al-`ulamā', yang berpendapat bahwa syarat dan indikator kesahīhan sanad hadis adalah sanadnya bersambung, rāwīnya berkualitas `ādil, rāwīnya dābit, terhindar dari shudhūdh, dan terhindar dari `illat. Hasil dari penelitian ini ditemukan 933 sumber hadis dari 151 hadis yang terdapat dalam Buku Fikih Kelas X, XI, dan XII. Setiap satu hadis diketemukan rata-rata 6,18 sumber hadis. Dari 151 hadis yang berkualitas Sahīh li Dhātihi sebanyak 101 (66,88%), Sahīh li Ghairihi sebanyak 2 (1,32%), Hasan li Dhātihi sebanyak 24 (15,89%), Hasan li Ghairihi sebanyak 2 (1,32%), dan Da’īf sebanyak 22 (14,57%)